1984
DOI: 10.1111/j.1423-0410.1984.tb03875.x
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Step Method for the Isolation of Antithrombin III1,2

Abstract: A single-step method is described for the isolation of a highly purified antithrombin III (AT III) concentrate at a recovery of over 30% using affinity chromatography on heparin-Sepharose (HS). The polyethylene glycol precipitation step frequently employed in the preparation of AT III concentrates for clinical use has been eliminated and purification is accomplished entirely by optimizing the salt concentration in the HS washing buffer to enhance the desorption of impurities prior to elution of AT III. Pasteur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This was removed by the second He parin Hyper D column. A similar result was observed by Wickerhauser and Williams [10], Known reasons for lowaffinity interaction of AT-III to heparin are: (a) cleavage of AT-III at the active site [24]; (b) folding into putative latent states by heat or chaotropes [22][23][24]; (c) aggregation fol lowing dénaturation [25]; (d) modification of the N-asparaginyl oligosaccharides from bianterinary to tetra-antennary structures in in vitro culture [26], and (e) point mutations of critical amino acids in the heparin binding region [1,27]. The latter two possibilities are not relevant to this situation.…”
Section: Discussionsupporting
confidence: 79%
“…This was removed by the second He parin Hyper D column. A similar result was observed by Wickerhauser and Williams [10], Known reasons for lowaffinity interaction of AT-III to heparin are: (a) cleavage of AT-III at the active site [24]; (b) folding into putative latent states by heat or chaotropes [22][23][24]; (c) aggregation fol lowing dénaturation [25]; (d) modification of the N-asparaginyl oligosaccharides from bianterinary to tetra-antennary structures in in vitro culture [26], and (e) point mutations of critical amino acids in the heparin binding region [1,27]. The latter two possibilities are not relevant to this situation.…”
Section: Discussionsupporting
confidence: 79%
“…Antithrombin III was purified from human plasma as described in Wickerhauser and Williams [20]. The purified ATIII was then linked to CNBr activated Sepahrose in the presence of excess N-acetylated Hp as in Höök et al ., [2].…”
Section: Methodsmentioning
confidence: 99%
“…Judging by the recovery of AT III activity and its appearance on two-dimensional immunoelectrophoresis, 0.35 M citrate added directly to the HS eluate (approximately 1.2 M NaCl) preserves AT III during pas teurization and gives results comparable with 0.5-1.0 M citrate in 0.15 M saline phos phate [18]. Since viruses, as well as AT III, may be protected by high concentrations of citrate and sodium chloride, it seems pru dent to use these in the lowest possible con centration.…”
Section: Hsmentioning
confidence: 98%
“…Since viruses, as well as AT III, may be protected by high concentrations of citrate and sodium chloride, it seems pru dent to use these in the lowest possible con centration. Only trials in chimpanzees or patients will prove whether this strategy is as effective in inactivating hepatitis viruses as is that used by Tabor et al [19], Wickerhauser and Williams [18] found that precipitation with 20% PEG removed all detectable HBsAg from the HS eluate and included this step as a precaution in addition to pasteuri zation. Since precipitation with PEG was not used in our method, there is an addi tional element of uncertainty about com plete inactivation of viruses and it cannot yet be claimed that this concentrate will not transmit hepatitis.…”
Section: Hsmentioning
confidence: 99%